2005
DOI: 10.1007/s00330-005-2819-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pancreatic exocrine function with secretin-enhanced magnetic resonance cholangiopancreatography: normal values and short-term effects of pancreatic duct drainage procedures in chronic pancreatitis. Initial results

Abstract: The aim of this study was to quantify pancreatic exocrine function in normal subjects and in patients with chronic pancreatitis (CP) before and after pancreatic duct drainage procedures (PDDP) with dynamic secretin-enhanced magnetic resonance (MR) cholangiopancreatography (S-MRCP). Pancreatic exocrine secretions [quantified by pancreatic flow output (PFO) and total excreted volume (TEV)] were quantified twice in ten healthy volunteers and before and after treatment in 20 CP patients (18 classified as severe, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 28 publications
(35 reference statements)
1
29
1
2
Order By: Relevance
“…The volume of pancreatic duct fluid, collected from the operating room in this study, is well within the volume that can be collected during ERCP following secretin stimulation. 38,39 The National Familial Pancreas Tumor Registry (NFPTR) tracks such families and analysis clearly demonstrates a prospective increased risk in first-degree relatives. 2,40 In Peutz-Jeghers syndrome, Giardiello's group has reported a 130 fold increased (95% CI, 44-261) relative risk of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of pancreatic duct fluid, collected from the operating room in this study, is well within the volume that can be collected during ERCP following secretin stimulation. 38,39 The National Familial Pancreas Tumor Registry (NFPTR) tracks such families and analysis clearly demonstrates a prospective increased risk in first-degree relatives. 2,40 In Peutz-Jeghers syndrome, Giardiello's group has reported a 130 fold increased (95% CI, 44-261) relative risk of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This increases its diagnostic potential in early and mild pancreatitis [27], as well as in congenital abnormalities, such as the pancreas divisum [28]. Different teams elaborated protocols in which SE-MRCP is used to assess the pancreatic fluid volume [29][30][31][32][33], which provides additional information on exocrine pancreatic function.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal fat concentration and a 13 C mixed-chain triglyceride breath test have also been compared to MRCP [9]. Dynamic changes including pancreatic exocrine secretions (quantified by pancreatic flow output and total excreted volume) have also been evaluated [6,21]. The Mayo Clinic group has reported that combining both endoscopic ultrasound and MRCP is highly predictive of early chronic pancreatitis and ERCP is unlikely to add any useful information [1].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) and variations in image processing such as diffusion weighting, dynamic thick slab and 3-D reconstruction are emerging as diagnostic tools to evaluate patients with suspected pancreatic disease [6]. MRI has a large appeal to generalists and subspecialists since it is completely non-invasive and does not induce procedure-related pancreatitis as its endoscopic counterpart – retrograde pancreatogram [7].…”
Section: Introductionmentioning
confidence: 99%